The diagnostic accuracy of circulating free DNA for the detection of KRAS mutation status in colorectal cancer: A meta‐analysis - Wenli Xie; Li Xie; Xianrang Song (Cancer Medicine)
Abstract KRAS mutations have been reported as a reliable biomarker for epidermal growth factor receptor (EGFR) targeted therapy and are also associated with poor prognosis in colorectal cancer (CRC) patients. However, limitations of detecting KRAS mutations in tissues are obvious. KRAS mutations in the peripheral blood can be detected as an alternative to tissue analysis. The objective of this meta‐analysis was to evaluate the diagnostic value of cfDNA (circulating free DNA) compared with tissues and to investigate the prognostic potential of cfDNA KRAS mutations in CRC patients. Searches were performed in PubMed, Embase, and Cochrane Library for published studies. We extracted true‐positive (TP), false‐positive (FP), false‐negative (FN), true‐negative (TN) values, survival rate of CRC patients with mutant and wild‐type KRAS and calculated pooled sensitivity and specificity, positive/negative likelihood ratios [PLRs/NLRs], diagnostic odds ratios [DORs], and corresponding 95% confidence intervals [95% CIs]. We also generated a summary receiver operating characteristic (SROC) curve to evaluate the overall diagnostic potential. Totally, 31 relevant studies were recruited and used for the meta‐analysis on the efficacy of cfDNA testing in detecting KRAS mutations. The pooled sensitivity, specificity, PLR, NLR, and DOR were 0.637 (95% CI: 0.607‐0.666), 0.943 (95% CI: 0.930‐0.954), 10.024 (95% CI: 6.912‐14.535), 0.347 (95% CI: 0.269‐0.447), and 37.882 (95% CI: 22.473‐63.857), respectively. The area under the SROC curve was 0.9392. Together, the results suggest that detecting KRAS mutations in cfDNA has adequate diagnostic efficacy in terms of specificity. There is a promising role for cfDNA in the detection of KRAS mutations in CRC patients. However, prospective studies with larger patient cohorts are still required before definitive conclusions of the prognostic potential of cfDNA KRAS mutations in CRC patients were drawn.